Gambaran tingkat kepatuhan ibu hamil mengkonsumsi tablet besi di wilayah kerja puskesmas Sidemen tahun 2015 - Sinthu Sivanganam; Wayan Westa (DiscoverSys Inc., 2017)
In Indonesia, prevention of anemia in pregnant women by providing as many as 90 tablets Fe supplements during pregnancy. However many pregnant women do not comply with this recommendation because of various reasons so anemia prevalence is still high. One of the factors that influence is the role of health care. This is important both as a source of information reliable as well as providers of medical services for prevention anemia in pregnant women. Detailed information about health services so. Pregnant women do not understand the dangers and the importance of giving iron tablets most of them assume that consuming Fe tablets can cause side effects so people tend to reject. This study was a Descriptive cross sectional to identify the level of compliance of pregnant women taking iron tablets knowing picture and information from health professionals about anemia and provision of iron tablets in the village of Sidemen. The results obtained from 50 respondents surveyed as many as 18 people (36%) out of 50 pregnant women in Sidemen village, Karangasem categorized obedient in consuming iron tablets, while as many as 32 people (64%) categorized as non-compliant